Seasonal and Spatial Variation in the Diet of Gambusia holbrooki in Different Water Bodies of Karaburun Peninsula (Western Türkiye) - Gülşah Saç; Sevan Ağdamar; Ümit Acar; Daniela Giannetto (Diversity)
The Eastern mosquitofish Gambusia holbrooki Girard, 1859, has been widely introduced into tropical and temperate countries as a biological agent to control mosquitos, which are associated with diseases such as malaria and yellow fever. However, the species exhibits invasive characteristics by competing with native species for food and habitat use. This study investigates the feeding ecology of G. holbrooki populations from three distinct freshwater environments (Lake Iris, Eğlenhoca Reservoir, and Parlak Reservoir) on the Karaburun Peninsula (North-Western Türkiye), a region outside its native range. The primary aim was to evaluate seasonal and spatial variations in the diet of the species. A total of 871 specimens were analysed: 247 from Iris Lake, 318 from Parlak Reservoir, and 306 from Eğlenhoca Reservoir. Low percentages of empty stomachs (≤20%) across all populations indicate high feeding intensity. The results reveal that G. holbrooki exhibits a generalist feeding strategy, consuming a wide range of food items such as insects, zooplankton, and plant material across all the investigated environments. The relative importance of food groups (determined by the Importance Index, MI%) varied seasonally but not spatially. In all three populations, the most important food source in the spring was dipterans, followed by plants in the summer and fall, and cladocerans in the winter. Plants accounted for the largest percentage of the diet in every population (MI% >65%). These findings suggest that G. holbrooki adapts its diet to seasonal food availability.